1995
DOI: 10.1159/000218570
|View full text |Cite
|
Sign up to set email alerts
|

Radio-Thermotherapy in Multimodal Surgical Treatment Concepts

Abstract: Hyperthermia can play a role in curative multimodal therapies of locally advanced malignancies. Firstly, the downstaging rate can be increased in pre-operative therapies (resectability, organ preservation), and secondly the local control can be improved. The synergistic effect of hyperthermia at 42-43 °C when combined with radiotherapy has been demonstrated in pre-clinical studies and in phase III studies as well. Furthermore, there are interactions with numerous cytotoxic drugs and un-specific as well as spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Here, both approaches could be used: a reduced radiotherapy dose, promoted by hyperthermia using the complex TER factor [81][82][83]. Different review articles have summarized the sensitizing effect on classical ionizing radiation by hyperthermia [80,[84][85][86]. Considerable success has been presented for hyperthermia in combination with radiotherapy for deep-seated tumors [87,, and success has also been observed in shallow tumors .…”
Section: Introduction and Interpretation Of A Relative "Old Method" Imentioning
confidence: 99%
“…Here, both approaches could be used: a reduced radiotherapy dose, promoted by hyperthermia using the complex TER factor [81][82][83]. Different review articles have summarized the sensitizing effect on classical ionizing radiation by hyperthermia [80,[84][85][86]. Considerable success has been presented for hyperthermia in combination with radiotherapy for deep-seated tumors [87,, and success has also been observed in shallow tumors .…”
Section: Introduction and Interpretation Of A Relative "Old Method" Imentioning
confidence: 99%
“…The heat-induced decrease of the DNA-dependent proteinkinase (DNA-PK), [121] is also a radio-sensitizer. Sensitizing the classical ionizing-radiation by hyperthermia has been well-known [122], [123] for a long time, and different review articles have summarized this knowledge [124], [125], [126], [127]. The advantage of combining heat-treatment with the classical ionizing-radiation is unambiguous, [128], [129], [84], the synergy between the methods is well known [130], [122] and successfully applied [131], [132], [106].…”
Section: The Heating Paradigmmentioning
confidence: 99%
“…To understand the action and mechanisms of hyperthermia and to develop optimal therapy modalities, biological phenomena as well as molecular metabolic and physiological events have to be considered [4,5]. Numerous basic studies have indicated that the antitumor effect of hyperthermia alone will not suffice and that there is a potential benefit when it is combined with radiation and chemotherapy.…”
Section: Concept Of Hyperthermiamentioning
confidence: 99%
“…The rationale for applying hyperthermia for cancer therapy with radiation is: 1) The S phase of the cell cycle is relatively radioresistant, hence it is sensitive to hyperthermia -and radiosensitization can be made selective by combining hyperthermia with irradiation; and 2) the relatively radioresistant hypoxic cells in the tumor may be selectively destroyed by the combination of hyperthermia and irradiation [6]. Data on hyperthermal sensitization effects are still incomplete, particularly its dependence on the time sequence and certain environmental factors (pH, pO 2 ) as well as its variation with the cell/tumor type [5]. The highest cytotoxic effect is observed when radiation is delivered simultaneously with heat, i.e.…”
Section: Concept Of Hyperthermiamentioning
confidence: 99%